La performativité du corps chez Deborah de Robertis. Ambivalences dans les espaces visuels du féminisme contemporain - Luc Schicharin (Genre, Sexualité et Société)
This article focuses on the performances of Deborah De Robertis who invests the visual space of the museum in order to criticize the sexist discourses of the art world that sexualize the female body in collections and current exhibitions. Our article aims to analyze the power relations the artist establishes with artistic institutions; it tries to understand how the artistic exhibition of her body/sex challenges the sexual passivity of women within artistic representation. We will also demonstrate that De Robertis’ performances make sense in relation to the corporeal practices of feminist art introduced in the 1960s, while recalling that this work adopts a contemporary posture that borrows its aesthetics from the contemporary feminist activism of Femen. Finally, we proceed to a critical examination of the aesthetics we have described as « Femen-ist » and which seem to us to be a source of ambivalences in the work of De Robertis because of the fascination she exercises on the media.